40.2k views
25 votes
Solve using substitution.

y = -5x - 1
y = -x - 5

User NTDLS
by
5.6k points

2 Answers

11 votes

Answer:

x=1 , y=-6

Explanation:

y=-5x-1 ..............1

y=-x-5 ...............2

1×y=-5x-1 .............3

5×y=-x-5................4

y= -5×-1

5y=-5×-5

-5-(-5)=0

y=-1

5y=-5

so; 4y=-1-(-5)

4y = 4

4

y = 1

sub y =1 into eqn................. 2

y=-x-5

y=-1-5

y= -6

User Hlib
by
4.6k points
3 votes

Answer:

x = 1 , y = -6

Explanation:

-5x - 1 = -x - 5

-5 x + x = -5 + 1

-4 x = -4

x = 1

if x = 1

y = -x - 5

y = -1 - 5

y = -6

User Kuvo
by
4.8k points